The effectiveness of microcontroller instructional system through simulation program method by using trainer kit - Edidas Edidas; Jalius Jama (REID (Research and Evaluation in Education), 2015)
The study was to test the learning effectiveness of program simulation method by using the trainer kit in Microcontroller System courses. The study was conducted to the students who took the microcontroller system courses in the academic year of 2013/2014. The students who took the course were divided into three groups and each of the group served as: (1) the experimental group; (2) control group; and (3) test instrument group. The learning outcome variables (Y2) and the awareness of thinkings (Y1) served as the dependent variable; on the other hand, the motivation (X1) and the creativity (X2) served as independent variables. The data analysis was done by performing the Analysis of Variance (ANOVA) and the Multivariate Analysis of Variance (MANOVA) in order to see the differences in the learning outcomes and the level of students thinking. The results of the study showed that there have been significant differences in the level of metacognition and the level of learning outcomes competence on the program simulation method by using the trainer kit on microcontroller systems course  in comparison to those who were not using it.